2021
DOI: 10.1088/1755-1315/782/3/032006
|View full text |Cite
|
Sign up to set email alerts
|

The limiting factor of land suitability for development of gambir cultivation (case-study in Sari Laba Jahe Village Deli Serdang North-Sumatra)

Abstract: Gambir-(Uncaria - gambir) -is commonly found in North Sumatera, especially in Pak-pak Bharat and Dairi Regency. This-study-aimed to determine the limiting factors for-gambir cultivation land suitability in Sari Laba Jahe Village, Sibiru-biru Sub-district, Deli Serdang Regency, North-Sumatera-Province. This study was-conducted from January 2020 to June 2020. Soil sampling based on land-unit was carried-out through a field survey to determine soil characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A land suitability assessment was performed, and the land was categorized into different suitability classes. The criteria for determining the suitability of growing S. benzoin were based on prior research findings, which are compiled and presented in a table (the land suitability characteristics of S. benzoin were derived from the "Valuable Sap of S. benzoin Booklet" published by the Ministry of Forestry, Forestry Research, and Development Agency, Aek Nauli Forestry Research Institute, Simalungun District, North Sumatra (Jayusman 2014;Silalahi and Sunandar 2017;Rahmawaty et al 2021aRahmawaty et al , 2023a (Tabel 1). Based on land evaluation process results, four distinct land suitability classes are established: highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N).…”
Section: Land Suitability Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A land suitability assessment was performed, and the land was categorized into different suitability classes. The criteria for determining the suitability of growing S. benzoin were based on prior research findings, which are compiled and presented in a table (the land suitability characteristics of S. benzoin were derived from the "Valuable Sap of S. benzoin Booklet" published by the Ministry of Forestry, Forestry Research, and Development Agency, Aek Nauli Forestry Research Institute, Simalungun District, North Sumatra (Jayusman 2014;Silalahi and Sunandar 2017;Rahmawaty et al 2021aRahmawaty et al , 2023a (Tabel 1). Based on land evaluation process results, four distinct land suitability classes are established: highly suitable (S1), moderately suitable (S2), marginally suitable (S3), and not suitable (N).…”
Section: Land Suitability Analysismentioning
confidence: 99%
“…in Humbang Hasundutan (Rahmawaty et al 2023a). Research conducted by Rahmawaty et al (2021b;2023a) regarding kemenyan and research conducted by et Rauf et al (2015); Rahmawaty et al (2021a;2023b) regarding gambir has indicated that kemenyan and gambir share similar land characteristics across various parameters. These criteria include factors, such as: temperature (tc), water availability (wa), root media (rc), nutrient retention (nr), and the erosion hazard (eh).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies on mapping the suitability of vegetables primarily utilized the top-down multi-criteria decision-making approaches that are subject to expert opinions (e.g., Widiatmaka, 2016;Rahmawaty et al, 2020Rahmawaty et al, , 2021Mugiyo et al, 2021;Zakaria et al, 2022). In these studies, the geospatial layers were first classified into suitability groups based on literature or expert knowledge.…”
Section: Figurementioning
confidence: 99%
“…Mostafiz et al (2021) applied a fuzzy membership method to map suitability of vegetables between different seasons in Bangladesh. Other studies had applied a top-down multi-criteria decision making to map suitability of vegetables without on-farm trial data (Mugo et al, 2016;Mostafiz et al, 2021;Rahmawaty et al, 2021;Yuniarti et al, 2022;Zakaria et al, 2022). Although multiple agencies in Tanzania promote sustainable vegetable farming at scale, detailed maps on the suitability of improved cultivars and related improved agronomic practices are lacking.…”
Section: Introductionmentioning
confidence: 99%